The more you lose the more you miss: accuracy of postpartum blood loss visual estimation. A systematic review of the literature. (2nd January 2018) - Natrella, Mariateresa; Di Naro, Edoardo; Loverro, Matteo; Benshalom-Tirosh, Neta; Trojano, Giuseppe; Tirosh, Dan; Besser, Limor; Loverro, Maria Teresa; Mastrolia, Salvatore Andrea
Abstract: Midwives and nurses have a key role in monitoring postpartum period. They represent the first line professional figure in quantifying blood loss, initiating early diagnosis of obstetric hemorrhage, and mobilizing a team response, if needed. These actions are crucial in determining maternal outcome in postpartum hemorrhage (PPH). In our review we aimed to: (1) Provide a picture of PPH including its pathophysiology, epidemiology, and associated complications; (2) Discuss diagnosis of this dangerous postpartum event; and, (3) Especially evaluate the efficiency of the employment of visual blood loss estimation as a rapid way to suspect PPH and activate the patient assessment.